Lutter contre le changement climatique ou pour son identité professionnelle? - Bertille Thareau; Mathilde Fabry; Arnaud Robin (VertigO)
This paper aims at interpreting on a sociological point of view the supposed lack of concern of farmers related to mitigation of climate change. Based on a survey of 29 farmers of west of France, our results show that most farmers have a confused and incomplete knowledge of theory of climate change and of its links with agriculture. But in the same time, ignoring it, most farmers have climate friendly practices. We show that the lack of interest in changing work practices is caused by farmer’s focus on the stakes involved in the risk climate change injunctions pose to their social hierarchies. Hence, for many farmers, climate change mitigation becomes a struggle to reassert the value of weakened professional identities.